2017
DOI: 10.1080/02699931.2017.1344121
|View full text |Cite
|
Sign up to set email alerts
|

The allocation of valenced concepts onto 3D space

Abstract: The valence-space metaphor research area investigates the metaphorical mapping of valenced concepts onto space. Research findings from this area indicate that positive, neutral, and negative concepts are associated with upward, midward, and downward locations, respectively, in the vertical plane. The same research area has also indicated that such concepts seem to have no preferential location on the horizontal plane. The approach-avoidance effect consists in decreasing the distance between positive stimuli an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 47 publications
4
16
0
Order By: Relevance
“…There is also evidence for associations between percepts and 2D space such that, for example, high-pitched sounds, which also have an associated positive valence, are mapped onto high spatial locations (Salgado-Montejo et al, 2016; but see Rusconi et al, 2006). By merging these results with those recently found by Marmolejo-Ramos et al (2018), we hypothesized that percepts are placed in 3D space in the same fashion as are valenced concepts. That is, positive percepts will be placed in high locations ( Y -axis) and near the participant’s body ( Z -axis), negative percepts will be placed in low locations and far from the participant’s body, and neutral percepts will be placed in between these percepts regarding both planes.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…There is also evidence for associations between percepts and 2D space such that, for example, high-pitched sounds, which also have an associated positive valence, are mapped onto high spatial locations (Salgado-Montejo et al, 2016; but see Rusconi et al, 2006). By merging these results with those recently found by Marmolejo-Ramos et al (2018), we hypothesized that percepts are placed in 3D space in the same fashion as are valenced concepts. That is, positive percepts will be placed in high locations ( Y -axis) and near the participant’s body ( Z -axis), negative percepts will be placed in low locations and far from the participant’s body, and neutral percepts will be placed in between these percepts regarding both planes.…”
Section: Introductionmentioning
confidence: 53%
“…This sample size was suggested by a power analysis for a general linear model with five fixed predictors that, as a full model, explained at least 25% of the variance in the dependent variable under a 5% Type I error (α) and an 80% power. (For details regarding the power estimation, see Marmolejo-Ramos et al, 2018) None of the participants reported any known visual, tactile, olfactory, auditory, or related sensory impairment. Forty percent of the participants were non-native Swedish speakers who reported good-to-excellent command of the English language.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a novel free-choice directional-step paradigm was used in the present study. This paradigm was inspired by experimental findings indicating that: (a) people tend to freely assign positive and negative concepts such as "happiness" or "unfriendly" to the lateral or sagittal space in line with the mentioned space-valence associations (e.g., Freddi et al, 2016;Marmolejo-Ramos et al, 2018), (b) congruent manual responses have also been shown facilitated after processing affective concepts (rightward-positive and leftward-negative; Milhau et al, 2015 or forward-positive and backward-negative; Freina et al, 2009), and (c) emotional visual stimuli (e.g., pictures) presented in front of participants facilitate congruent approach-avoidance step actions (e.g., forward step-positive; backward step-negative; e.g., Stins and Beek, 2011). However, these findings are based on studies that typically address the lateral and sagittal spatial dimensions independently from each other.…”
Section: Discussionmentioning
confidence: 99%
“…There is experimental evidence supporting such associations. For example, akin to findings addressing the lateral (and vertical) space, it has been shown that when asked to freely choose a location within an empty cube positioned in front of them, participants tend to assign positive words (e.g., "open-minded") at closer areas with regard to their body and negative words (e.g., "insolent") at farther ones (Marmolejo-Ramos et al, 2018).…”
Section: Valence Associations Across the Lateral Space: The Affectivementioning
confidence: 99%